Impact of Previous Nephrectomy on Clinical Outcome of Metastatic Renal Carcinoma Treated With Immune-Oncology: A Real-World Study on Behalf of Meet-URO Group (MeetUro-7b) - Stellato, Marco; Santini, Daniele; Verzoni, Elena; De Giorgi, Ugo; Pantano, Francesco; Casadei, Chiara; Fornarini, Giuseppe; Maruzzo, Marco; Sbrana, Andrea; Di Lorenzo, Giuseppe; Soraru, Mariella; Naglieri, Emanuele; et al. (Frontiers in Oncology, 2021)
Background Immune-Oncology (IO) improves Overall Survival (OS) in metastatic Renal Cell Carcinoma (mRCC). The prognostic impact of previous Cytoreductive Nephrectomy (CN) and radical nephrectomy (RN) with curative intent in patients treated with IO is not well defined. The aim of our paper is to evaluate the impact of previous nephrectomy on outcome of mRCC patients treated with IO. Methods 287 eligible patients were retrospectively collected from 16 Italian referral centers adhering to the MeetUro association. Patients treated with IO as first line were excluded. Kaplan-Meier method and log-rank test were performed to compare Progression Free Survival (PFS) and OS between groups. In our analysis both CN and RN were included. The association between nephrectomy and other variables was analyzed in univariate and multivariate setting using the Cox proportional hazard model. Results 246/287 (85.7%) patients had nephrectomy before IO treatment. Median PFS in patients who underwent nephrectomy (246/287) was 4.8 months (95%CI 3.9-5.7) vs 3.7 months (95%CI 1.9-5.5) in patients who did not it (HR log rank 0.78; 95%CI 0.53 to 1.15; p=0.186). Median OS in patients who had previous nephrectomy (246/287) was 20.9 months (95%CI 17.6-24.1) vs 13 months (95%CI 7.7-18.2) in patients who did not it (HR log rank 0.504; 95%CI 0.337 to 0.755; p=0.001). In the multivariate model, nephrectomy showed a significant association with OS (HR log rank 0.638; 95%CI 0.416 to 0.980), whereas gland metastases were still associated with better outcome in terms of both OS (HR log rank 0.487; 95%CI 0.279 to 0.852) and PFS (HR log rank 0.646; 95%CI 0.435 to 0.958). Conclusions IO treatment, in patients who had previously undergone nephrectomy, was associated with a better outcome in terms of OS. Further prospective trials would assess this issue in order to guide clinicians in real word practice.